Management of Legg–calve–perthes Disease with Acupuncture: A Case Report. Issue 1 (March 2013) - Set, Turan; Maras, Ismail; Khan, Abdul Sattar; Ozdemir, Hakan
Legg–Calve–Perthes disease (LCPD) is a rare temporary hip joint deformity mostly effecting young children from 4–10 years of age. It involves mainly the head of the femur, which softens and breaks down due to interruption of blood supply (avascular necrosis). We report a case of LCPD that was treated late and had a poor prognosis, but improved significantly during a prolonged course of acupuncture. A 12-year-old boy reported to an orthopaedic clinic in 2006 with limping and was diagnosed with LCPD. Surgeons applied orthosis without improvement and decided to perform surgery in 2008. However, the parents declined the surgical option and took the boy to an acupuncture clinic the same year. Needle acupuncture for 20 min and laser acupuncture locally on the hip joint area for 5 min were applied. After 30 sessions of acupuncture, the boy started to improve clinically. Imaging studies showed that new bone cells started to develop in the femoral head. After 130 sessions in 2010 the radiographic appearance showed almost 90% improvement, and after 196 sessions, in August 2012, he was fully recovered. Needle acupuncture treatment combined with laser acupuncture may be an option for the management of LCPD.